Design of â€œSpinner Pulling Oilâ€ as an Automatic Oil Removal to Increase Quality of Catfish (Pangasius pangasius) Floss in Koperasi Wanita Srikandi - Nugraha, Muhammad Agung; Felayati, Helmi Fadhlurrahman; Irianto, Alvian Budhi; Susilo, Bambang; Lutfi, Musthofa; Sugiarto, Yusron (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
Banturejo that is located in Kecamatan Ngantang, Kabupaten Malang, East Java Province, has a potential commodity in fisheries. The local resident see this potential commodity as a business opportunity by producing several kind of food products. KOPWAN Srikandi, which is women corporation, sell food products from fresh fish material. One of the products is catfish (Pangasius pangasius) floss. The problem production is the quality of fish floss which contain high level of oil content. Therefore it makes shelf life of catfish floss is relatively short. â€œSpinner pulling oilâ€ is an automatic removal oil device which is equipped by centrifugal force to reduce the high level of oil content and become a solution to solve the problems on a household industries. Spinner Pulling Oil equipped with timer that able to automation and dimensions used for the design are Length x Width x Height is 60 x 45 x 52 centimeters. The driving tool with an electric motor that is used has the power Â¼ HP, 2.36 A with 220 V of voltage, 50 Hz, 1400 RPM (1 phase motor) and 200 watt so it can move the material basket with a capacity of 10 kg at a speed of 1076 RPM. Performance testing of spinner was carried out to determine the machine performance with trial to the machine and by doing the test of the oil content of sample after spinning. The sample of catfish floss was threatened with the difference time duration included 0, 2, 4, 6, 8 and 10 minutes. In this study, the time optimal and the power consumption of device was being analyzed. The optimal time of spinning was obtained in 6 min with 25,49% fat content. Â Keyword : Banturejo Village,Fish Floss, Spinner Pulling Oil